-2(-f+11)=-13+2f-9

Simple and best practice solution for -2(-f+11)=-13+2f-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-f+11)=-13+2f-9 equation:


Simplifying
-2(-1f + 11) = -13 + 2f + -9

Reorder the terms:
-2(11 + -1f) = -13 + 2f + -9
(11 * -2 + -1f * -2) = -13 + 2f + -9
(-22 + 2f) = -13 + 2f + -9

Reorder the terms:
-22 + 2f = -13 + -9 + 2f

Combine like terms: -13 + -9 = -22
-22 + 2f = -22 + 2f

Add '22' to each side of the equation.
-22 + 22 + 2f = -22 + 22 + 2f

Combine like terms: -22 + 22 = 0
0 + 2f = -22 + 22 + 2f
2f = -22 + 22 + 2f

Combine like terms: -22 + 22 = 0
2f = 0 + 2f
2f = 2f

Add '-2f' to each side of the equation.
2f + -2f = 2f + -2f

Combine like terms: 2f + -2f = 0
0 = 2f + -2f

Combine like terms: 2f + -2f = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4y+11=-y+7 | | Lg(3x-5)=3 | | .15*x=298 | | X-51=100 | | 2r^4+46r^2=0 | | (4x+6)*4=88 | | 5+35x=28x+7 | | 4(0.75n+1)=5-2(n-0.50) | | 16y-27=13 | | x^2+24.933x-305.4=0 | | -7+-w=-10 | | 6x+0.4=42.4 | | x^2+25x-305=0 | | 2x+35+x-2=180 | | x^2-25x+305=0 | | -c+4c+7=7-c+8c | | -4+2s=4 | | 10+6k= | | 12x=9.12 | | -4=-12+4n | | -8+1x=-1x+20 | | a3*a2/a5= | | 7x+4y=61 | | 14m+5n-4m+9n= | | 17-20b=4(-13-5b) | | q^2-16q+275=0 | | 4 = v-2+ 5 | | 16/140=x/60 | | 5b+6=132-10 | | (2x+1)+x+13=72 | | -6(x-7)=66 | | 14m+5n-4m+9m= |

Equations solver categories